Quantitative single-molecule imaging of TNFR1 reveals zafirlukast as antagonist of TNFR1 clustering and TNFα-induced NF-ĸB signaling. Issue 2 (13th May 2020) - Weinelt, Nadine; Karathanasis, Christos; Smith, Sonja; Medler, Juliane; Malkusch, Sebastian; Fulda, Simone; Wajant, Harald; Heilemann, Mike; van Wijk, Sjoerd J L
Abstract: TNFR1 is a crucial regulator of NF-ĸB-mediated proinflammatory cell survival responses and programmed cell death (PCD). Deregulation of TNFα- and TNFR1-controlled NF-ĸB signaling underlies major diseases, like cancer, inflammation, and autoimmune diseases. Therefore, although being routinely used, antagonists of TNFα might also affect TNFR2-mediated processes, so that alternative approaches to directly antagonize TNFR1 are beneficial. Here, we apply quantitative single-molecule localization microscopy (SMLM) of TNFR1 in physiologic cellular settings to validate and characterize TNFR1 inhibitory substances, exemplified by the recently described TNFR1 antagonist zafirlukast. Treatment of TNFR1-mEos2 reconstituted TNFR1/2 knockout mouse embryonic fibroblasts (MEFs) with zafirlukast inhibited both ligand-independent preligand assembly domain (PLAD)-mediated TNFR1 dimerization as well as TNFα-induced TNFR1 oligomerization. In addition, zafirlukast-mediated inhibition of TNFR1 clustering was accompanied by deregulation of acute and prolonged NF-ĸB signaling in reconstituted TNFR1-mEos2 MEFs and human cervical carcinoma cells. These findings reveal the necessity of PLAD-mediated, ligand-independent TNFR1 dimerization for NF-ĸB activation, highlight the PLAD as central regulator of TNFα-induced TNFR1 oligomerization, and demonstrate that TNFR1-mEos2 MEFs can be used to investigate TNFR1-antagonizing compounds employing single-molecule quantification and functional NF-ĸB assays at physiologic conditions. Graphical Abstract: Validates and characterizes membrane TNFR1 clustering antagonists using quantitative super-resolution microscopy with single-molecule resolution at physiological levels.